Statistics in criminology and criminal justice: analysis and interpretation - Walker, Jeffery T. (Jones and Bartlett Publishers, 2009)
The logic of comparisons and analysis -- Variables and measurement -- Understanding data through organization: summarizing data in tables, frequency distributions, and graphical representation -- Measures of central tendency -- Measures of dispersion -- The form of a distribution -- Introduction to bivariate descriptive statistics -- Measures of existence and statistical significance -- Measures of strength of a relationship -- Measures of direction and nature of a relationship -- Introduction to multivariate statistics -- Multiple regression 1: ordinary least squares regression -- Multiple regression 2: limited dependent variables -- Factor analysis, path analysis, and structural equation modeling -- Introduction to inferential analysis -- Hypothesis testing -- Hypothesis tests -- Analysis of variance (ANOVA) -- Putting it all together -- Appendix A Math review and practice test -- Appendix B Distribution of f; p=.05 -- Appendix C